Aero-acoustics Investigation of a Bionic Airfoil Horizontal Axis Wind Turbine Using LES-DCS Approach. Issue 1 (1st June 2022) - Wu, Weimin; Dong, Wenling; Li, Shiwei; Zhang, Suocheng
Abstract: The wind turbine noise has become an important issue in the current green energy field, therefore, it is necessary to use new and advantageous methods to study the problem. This research employed the LBM-DCS method to investigate the wake sound radiation characteristics for a bionic airfoil horizontal axis wind turbine, combining the large eddy simulation (LES) model and the wall-adapting local eddy-viscity (WALE) model. The obtained results show that the aeroacoustic model used here is reasonable and effective, which are consistent with the relevant experimental measurement result. The appearance and changing characteristics of the acoustic radiation ring have been discussed and analyzed to a certain extent. Based on the accumulation of this research, we will combine more experimental data to carry out a further systematic investigation on the acoustic radiation characteristics to the wind turbine.